Interacting land use and soil surface dynamics control groundwater outflow in a montane catchment of the lower Mekong basin - Ribolzi, Olivier; Lacombe, Guillaume; Pierret, Alain; Robain, Henri; Sounyafong, Phabvilay; de Rouw, Anneke; Soulileuth, Bounsamai; Mouche, Emmanuel; Huon, Sylvain; Silvera, Norbert; Latxachak, Keo Oudone; Sengtaheuanghoung, Oloth; et al. (Agriculture, ecosystems & environment, 2018)
Stream-hillslope connectivity controlled by crop-fallow cycle and soil crust. [Display omitted] •Annual runoff coefficient decrease with fallow regrowth.•Rain infiltration is limited by soil surface crusting under annual crops.•Groundwater outflow during storms increase with soil crusting rate reduction.•Soil features and land use mosaic determine preferential pathways of water.•Stream-hillslope connectivity dynamic controlled by crop-fallow cycle and soil crust. Groundwater contribution to streamflow sustains biodiversity and enhances ecosystem services, especially under monsoon-driven climate where stream baseflow is often the only available water resource during the dry season. We assessed how land use change influences streamflow and its groundwater contribution in a small headwater catchment subject to shifting cultivation in Montane Southeast Asia. Continuous time series of rainfall, reference evapotranspiration, groundwater level, stream discharge and electrical conductivity (EC) of surface and groundwater were monitored from 2002 to 2007. With the rainfall-runoff model GR4J, we investigated temporal changes in the hydrological behaviour of the study catchment to verify consistencies with observed land use change. An EC-based hydrograph separation method allowed estimating the groundwater contribution to 104 stormflow events. Mean soil surface crusting rates corresponding to each of the nine land uses identified in the catchment were determined using 236 standard 1-m2 micro-plots. Mean plant cover for each land use was assessed in 10 × 10-m2 plots. Bedrock topography and soil layers’ structure were assessed by electrical resistivity tomography to determine pathways of subsurface storm flows. Our results indicate that an increase in the catchment's areal percentage of fallow from 33% to 71% led to a decrease in the annual runoff coefficient from 43% to 26%. The concurrent reduction of soil crusting rate over the catchment, from 48% to 30%, increased rainwater infiltration. Consecutively, groundwater contribution to storm streamflow increased from 83% to 94%, highlighting the protective role of a dense vegetation cover against flash floods. The overall reduction of the annual basin water yield for inter-storm streamflow from 450 to 185 mm suggests that the potential gain in groundwater recharge was offset by the increased root water uptake for evapotranspiration, as confirmed by the drop in the groundwater level. This analysis illustrates how two different land uses with opposite impacts on soil permeability (i/ extensive soil surface crusting under annual crops resulting in limited runoff infiltration or ii/ fallow regrowth promoting both infiltration and evapotranspiration) both inhibit groundwater recharge. The maintenance of strips of fallow buffers between annual crop plots can slow down runoff and locally promote infiltration and groundwater recharge while limiting evapotranspiration.